MULTIPLE SHOOT REGENERATION VIA INDIRECT ORGANOGENESIS FROM SHOOT TIP AND NODAL MERISTEM EXPLANTS OF CERATOPHYLLUM DEMERSUM L. - M. Dogan (Journal of Animal and Plant Sciences, 2019)
Ceratophyllum demersum L. (Ceratophyllaceae) is a well-known medicinal plant. The objective of this study was to improve an effective protocol for in vitro callus formation and plantlet regeneration using shoot tip and different nodal explants of C. demersum and to investigate the changes in the photosynthetic pigment contents of shoots emerging from these calli. Murashige and Skoog (MS) media having various concentration of thidiazuron (TDZ, 0.05-0.80 mg/L) were tested for callus induction. With the effect of TDZ, callus induction occurred at high frequency from the explants. Callus regeneration frequencies were determined as 100% in all culture media for 1st nodal explant, as 83-100% for shoot tip and as 66-100% for 2nd nodal explant. The best hormone application in terms of callus concentrations was found as MS medium containing 0.50 and 0.75 mg/L TDZ for all explants. In the second phase, the calli derived from the explants transferred to free-hormone MS (MSO) and MS medium supplemented with 0.10 mg/L 6-Benzylaminopurine (BAP) and 0.10 mg/L Gibberellic Acid (GA3) for shoot regeneration. Multiple shoot regenerations from subcultured callus in different media were successfully achieved. Maximum number of shoots per callus from shoot tip (108), 1st (96) and 2nd (87) nodal meristem explants were recorded on MS medium fortify with 0.10 mg/L GA3. The longest shoots were obtained in the MS medium containing 0.10 mg/L GA3 for the 1st (1.39 cm) and 2nd (1.43 cm) nodal explants and in the MS medium containing 0.10 mg/L BAP for the shoot tip explants (1.25 cm). The highest chlorophyll a, b and total chlorophyll contents of regenerated shoots were obtained in shoot tip callus cultured in MS medium fortify with 0.10 mg/L BAP, while the maximal carotenoid content was determined in 2nd nodal callus cultured in MS medium supplemented with 0.10 mg/L GA3. It has been found that the regenerated shoots from the shoot tip callus had higher chlorophyll content. This study is a new protocol for the efficient and rapid production of C. demersum via callus induction and showed that high efficiency production system can be established for C. demersum.
Keywords: Callus induction; C. demersum; nodal explant; photosynthetic pigment